Orchidaceae neotropicales, ii: de orchidaceis principaliter colombianis notulae (1957)
During the past fifteen or twenty years, plant exploration in Colombia has been greatly intensified. The number of collections, especially from the high Andean regions of the country, is now very much more comprehensive; and monographic. and floristic projects should find in this trend strong impetus and keen encouragement. The very task of routine identification of plant collections often uncovers significant information. Frequently, species or genera turn up which are new either to Colombia or to a given phytogeographic province of the country.